NLRP3 inflammasome activation in response to metals - Huang, Wanyi; Zhang, Ziqi; Qiu, Yueyang; Gao, Yuan; Fan, Yongqiang; Wang, Qiang; Zhou, Qing (Frontiers in Immunology, 2023)
Implant surgery follows a series of inflammatory reactions, which directly affect the postoperative results of surgery. Inflammasome plays a vital role in the inflammatory response by inducing pyroptosis and producing interleukin-1β, which plays a critical role in inflammation and tissue damage. Therefore, it is essential to study the inflammasome activation in the bone healing process after implant surgery. As the primary material of implant, the metals-inducing local inflammatory reaction has received significant attention and there is more and more research on the NLRP3 inflammasome activation caused by metal materials. In this review, we consolidate the basic knowledge about the NLRP3 inflammasome structures, the present knowledge about the mechanisms of NLRP3 inflammasome activation and the studies of metals-induced NLRP3 inflammasome activation.